2006
DOI: 10.1007/s00441-006-0189-1
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant profile of gene expression in cloned mouse embryos derived from donor cumulus nuclei

Abstract: Somatic cell nuclear transfer has successfully been used to clone several mammalian species including the mouse, albeit with extremely low efficiency. This study investigated gene expression in cloned mouse embryos derived from cumulus cell donor nuclei, in comparison with in vivo fertilized mouse embryos, at progressive developmental stages. Enucleation was carried out by the conventional puncture method rather than by the piezo-actuated technique, whereas nuclear transfer was achieved by direct cumulus nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 84 publications
5
15
0
Order By: Relevance
“…This finding supports a relationship between incidence of cell death and developmental potential as indicated by the lower developmental rate in NT embryos derived from FF. Aberrant gene expression is frequently observed in NT embryos of mouse, bovine, and porcine, and is one of the suggested causes of the low success rates of this approach (Boiani et al, 2002;Bortvin et al, 2003;Zhu et al, 2004;Miyazaki et al, 2005;Li et al, 2005;Tong et al, 2006). Examination of the gene expression pattern in NT embryos would aid in determining the causes of such abnormal development.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding supports a relationship between incidence of cell death and developmental potential as indicated by the lower developmental rate in NT embryos derived from FF. Aberrant gene expression is frequently observed in NT embryos of mouse, bovine, and porcine, and is one of the suggested causes of the low success rates of this approach (Boiani et al, 2002;Bortvin et al, 2003;Zhu et al, 2004;Miyazaki et al, 2005;Li et al, 2005;Tong et al, 2006). Examination of the gene expression pattern in NT embryos would aid in determining the causes of such abnormal development.…”
Section: Discussionmentioning
confidence: 97%
“…A favored hypothesis for the developmental incompetence of clones is inadequate reprogramming of the transplanted nucleus to a state equivalent to that of an early embryonic nucleus. Nuclear reprogramming of donor cells (within the ooplasm) is a complex process involving the orderly switching off and on of a diverse array of somatic and embryonic genes, to support embryogenesis and concomitant developmental events (Tong et al, 2006). It is likely that inappropriate expression of key developmental genes may contribute to the lethality of cloned embryos (Li, 2002;Jaenisch et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The complete reprogramming required for normal development is induced in only a few cases; consequently, faulty epigenetic changes accompanied by diverse abnormalities in the development of somatic/embryonic stem cell nuclear transferred (SECNT) embryos occur very frequently [13], [14], [15], [16], [17], [18]. Research on pre- and postimplantation development of SECNT embryos has shown that the embryos rapidly lose their developmental ability around the time of implantation, resulting in failure of implantation and normal embryogenesis [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that histone methylation may be involved in embryonic gene expression. Tong et al reported that several genes required for embryonic development are aberrantly expressed in cloned mouse embryos [18]. However, it is unclear whether aberrant gene expression in cloned embryos is directly related to epigenetic reprogramming.…”
mentioning
confidence: 99%